ANALISIS RESEPSI KHALAYAK TERHADAP KONTEN IKLAN RABBANI "RE-ARIS3" PADA INSTAGRAM (STUDI PEMAKNAAN KHALAYAK TERHADAP PESAN BERPAKAIAN DAN PELECEHAN SEKSUAL) - Raihan Attala (2024)
Through Stuart Hall's reception theory, this research aims to see the audience's interpretation of information about the phenomenon of sexual harassment on Rabbani's Instagram account. The researcher focuses on the content of the @rabbaniprofesorkerudung Instagram account which discusses sexual harassment and its relationship with women's clothing. This information needs to be understood, especially by female audiences, in relation to raising awareness in society about the issue of this harassment phenomenon. This research focuses on how individuals receive information regarding sexual harassment and its relationship with women's clothing, using the reception analysis method and utilizing primary and secondary data sources to examine how individuals interpret and understand the advertising content aired on the @rabbaniprofesorkerudung Instagram account. The sampling technique used purposive sampling and involved three main elements in the reception methodology, namely data collection, analysis, and interpretation. Researchers ensured data validity through source triangulation. Informants were categorized based on Stuart Hall's position of meaning: dominant hegemony position, negotiation position, and opposition position. The results showed that of the five informants, one person was in the Dominant position, three people were in the Negotiation position, and one person was in the Opposition position. The informants' backgrounds, including education, life experience, and level of knowledge about sexual harassment, affect the different meanings conveyed.